Pottery craft development: Upgrading the traditional combustion management patterns for product quality and aesthetics in Pagelaran Village, Malang - Aini, Desti Nur; Winarno, Agung; Arsadi, Arsadi; Mohd Salleh, Norlida Hanim (citeus, 2023)
This study examines the process of improving the quality of pottery products from Pagelaran village in Malang mainly by improving the traditional combustion process. The traditional pottery craftsmen in this area have faced issues with both the aesthetic values and quality standard of their products, even having defective products due to poor processes. Despite these challenges, pottery craft in Pagelaran is considered a cultural heritage that has contributed to the welfare of craftsmen and the local community, as well as the preservation of local wisdom. To improve the quality of their products, the craftsmen in Pagelaran have focused on the way they use tools and materials, the technical production process by linking technology and the environment, the method used, and the effect on future environmental changes. This study employs a descriptive qualitative and action research, which involves the craftsmen community in Kampung Edukasi Wisata. Data is collected through observation and in-depth interviews and analyzed using the 6P simultaneous stages technique proposed by Winarno and Robfiah (2020). The findings of the study show that while the tools and materials used in the pottery production are still traditional, the pottery of Pagelaran is leading to innovative aesthetic products. Pottery production activities have an impact on the physical environment, requiring technology, methods, and cultural impact in the exploitation of the environment under the cultural ecology perspective. Despite the traditional production process, it has been integrated with user demands so that the quality of the product is improved through the standardization of the combustion process, product decoration, and additional touches of aesthetic values on the products. Overall, this study provides insights into how traditional craftsmen can improve their product quality through a focus on both the technical production process and cultural impact.